Role of big data in agriculture- A statistical prospective - Kumar, Prakash; Kumar, Anil; Panwar, Sanjeev; Dash, Sukanta; Sinha, Kanchan; Chaudhary, Vipin Kumar; Ray, Mrinmoy (Annals of Agricultural Research, 2019)
Data are playing an important role making good planning and policies for agricultural growth and development. Population growth and climate change are worldwide trends that are increasing the importance of using big data science to improve agriculture. Add to that land degradation increasing marginal land and loss of biodiversity are better deals with study of big data science. Crop data can be break down into bits and bytes it will give better study about the crop development by using advance data analytics tools for betterment of agriculture. Here, talk about some important tools and techniques to handle and study the big data.